Reinterpreting Residential Enclosed Open Space Of Lahore: A Study Into Elderly Occupant Perception - Fatima Nasir Alvi; Dr. Saima Gulzar; Dr. Syed Faisal Sajjad; Sobia Razzak; Mahrukh Rehman Mirza; Rimsha Imran; Fareena M. Ehsan; Muhammad Faran Saleem (Kurdish Studies, 2024)
This study aims to address the effect of residential enclosed open space, the courtyard on the psychological and physiological wellbeing of the Pakistan’s elderly residents aged sixty-five and above, highlighting how the absence of such spaces leads to a disconnect from nature, fostering feelings of gloom and emptiness among them. Qualitative questionnaire survey method is employed and respondents from both genders were interviewed through purposeful sampling. The findings and the conclusions lead to recommendations. Ultimately, this research aims to highlight the necessity of incorporating enclosed open spaces in residential designs to enhance the overall well-being of elderly residents.